Incidence and distribution of seed-borne viruses of chickpea and faba bean seeds in Tunisia - Najar, Asma; Mghandef, Samia; Kumari, Safaa (International Center for Agricultural Research in the Dry Areas, 2024)
The study investigates the incidence and distribution of seed-borne viruses in faba bean and chickpea crops in Tunisia, focusing on their economic and agricultural significance. Seed samples from 20 locations across Tunisia were tested using tissue-blot immunoassay (TBIA) for six viruses: Broad Bean Mottle Virus (BBMV), Broad Bean Stain Virus (BBSV), Pea Seed-borne Mosaic Virus (PSbMV), Bean Yellow Mosaic Virus (BYMV), Alfalfa Mosaic Virus (AMV), and Cucumber Mosaic Virus (CMV). Among 4,587 faba bean seedlings, only BYMV was detected in two seed lots with a seed transmission rate of 1.7%. For 4,000 chickpea seedlings, AMV and PSbMV were identified in three and nine seed lots, respectively, with seed transmission rates of 1.0% and 3.2%. The highest PSbMV transmission rate (8.3%) was found in two chickpea lots. These findings underscore the need for regular monitoring, improved seed quality, and further research to mitigate virus transmission and enhance crop productivity in Tunisia.